2001
DOI: 10.1111/j.1574-6941.2001.tb00768.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron metabolism in anoxic environments at near neutral pH

Abstract: Anaerobic dissimilatory ferric iron-reducing and ferrous iron-oxidizing bacteria gain energy through reduction or oxidation of iron minerals and presumably play an important role in catalyzing iron transformations in anoxic environments. Numerous ferric iron-reducing bacteria have been isolated from a great diversity of anoxic environments, including sediments, soils, deep terrestrial subsurfaces, and hot springs. In contrast, only few ferrous iron-oxidizing bacteria are known so far. At neutral pH, iron miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
196
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(202 citation statements)
references
References 46 publications
6
196
0
Order By: Relevance
“…This regulatory mechanism, which is independent of the redox potential, is also mirrored in the strategy of respiratory periplasmic branching initiated by the cytoplasmic membrane protein CymA. The electron transfer chains to DMSO (DMSO/DMS: þ 160 mV), nitrate (NO 3 À /NO 2 -: þ 433 mV), nitrite (NO 2 À /NH 4 þ : þ 340 mV), ferric iron ( þ 372 to À 177 mV), manganese oxide (Mn 4 þ /Mn 2 þ : þ 612 to þ 269 mV) and fumarate (fumarate/succinate: þ 33 mV) all rely on this menaquinol oxidase (Thauer et al, 1977;Straub et al, 2001). This might be an adaptation to environments such as sediments in which rapid redox cycling occurs.…”
Section: Discussionmentioning
confidence: 99%
“…This regulatory mechanism, which is independent of the redox potential, is also mirrored in the strategy of respiratory periplasmic branching initiated by the cytoplasmic membrane protein CymA. The electron transfer chains to DMSO (DMSO/DMS: þ 160 mV), nitrate (NO 3 À /NO 2 -: þ 433 mV), nitrite (NO 2 À /NH 4 þ : þ 340 mV), ferric iron ( þ 372 to À 177 mV), manganese oxide (Mn 4 þ /Mn 2 þ : þ 612 to þ 269 mV) and fumarate (fumarate/succinate: þ 33 mV) all rely on this menaquinol oxidase (Thauer et al, 1977;Straub et al, 2001). This might be an adaptation to environments such as sediments in which rapid redox cycling occurs.…”
Section: Discussionmentioning
confidence: 99%
“…4a-c), exospore-like features (Fig. 4b,d) and fossilization mechanism, we interpret as fossil relatives of the anoxygenic photoferrotroph, Rhodomicrobium vanielii 7,8,23,24 . Similar to their modern counterparts, these microorganisms grew by polar budding, forming vast networks of cells connected end-to-end by stalk appendages, when transforming Fe 2 þ to Fe 3 þ during anoxygenic photosynthesis.…”
Section: Geology and Geochemistry The Cape Vani Rocks (mentioning
confidence: 99%
“…Instead, biotic, anoxygenic photoferrotrophic precipitation according to the equation 4Fe 2 þ þ CO 2 þ 11H 2 O þ light-[CH 2 O] þ 4Fe(OH) 3 þ 8H þ has been proposed [6][7][8][9][10][11][12][13][14] . With the exemption of proxies such as iron isotopes 12,13 , there exists no direct environmental evidence-neither in ancient nor in modern ecosystems-demonstrating how photoferrotrophs could have accounted for vast-scale biological BIF deposition, including the formation of their spectacular banded consistency.…”
mentioning
confidence: 99%
“…Hence, the microbial reduction of most metals has commonly been studied in anoxic environments instead of aerobic conditions (Straub et al 2001). Only recent research has reported that metal-reducing bacteria such as Pseudomonas and Shewanella have the ability to reduce Cr (VI) to Cr(III) in the presence of oxygen (McLean and Beveridge 2001;Middleton et al 2003;Wani et al 2007).…”
Section: Introductionmentioning
confidence: 99%